Rifftide : The Life and Opinions of Papa Jo Jones - Jones, Papa Jo (Book collections on Project MUSE., 2011)
"The things that I have, I'll give to you. This is my legacy with you, Albert. This is my last hoo-rah. "So begins the autobiography of Jonathan David Samuel Jones--or as the world better knows him, Papa Jo Jones. Playing with Count Basie and his orchestra when they exploded out of Kansas City in 1936 and took the world by storm, Jones went on to inspire generations of jazz drummers, but until now few have had access to his own remarkable story. "Rifftide" presents Jones's inimitable life and opinions, as originally told by Jones to the prominent jazz historian and novelist.